STRATEGI BERTAHAN HIDUP INDUSTRI KECIL AGRO PASCA PANDEMI COVID 19 DI INDONESIA: ANALISIS BERBASIS KETAHANAN - Anne Charina; Rani Andriani Budi Kusumo; Gema Wibawa Mukti (Universitas Galuh, 2023)
COVID-19 has caused severe damage in various sectors of the world. The economic sector is a sector that is severely affected, especially small-scale industries. However, it turns out that there are still small industries that can survive in the midst of the pandemic that hit. This study identified small industrial survival strategies after the Covid-19 pandemic in West Java, Indonesia. This research adopts qualitative research techniques, through double Kasus study techniques. The data collection consists of personal interviews of 20 small agro industry entrepreneurs, through the exploration of personal stories and direct observation and analysis of documents. Qualitative descriptive analysisis used to analyze the data obtained. This research reveals that the survival strategy carried out by small industries post the Covid-19 pandemic in Indonesia is based on self-resilience. This highlights how processes and strategies rise from the downturn caused by covid. Self-resilience will be formed from attitudes of personal competence, strandar to advance and tenacious, Trust in one's instincts, tolerance of negative affect, and strengthening effects of stress, Positive acceptance of change, and secure relationships, control and Spiritual influences. This strategy is a very important basic stage for small industries to rise from the Covid-19 pandemic.